Human Adipose Tissue Derived Stem Cells Promote Liver Regeneration in a Rat Model of Toxic Injury. (7th November 2013) - Koellensperger, Eva; Niesen, Willem; Kolbenschlag, Jonas; Gramley, Felix; Germann, Guenter; Leimer, Uwe
Abstract : In the light of the persisting lack of donor organs and the risks of allotransplantations, the possibility of liver regeneration with autologous stem cells from adipose tissue (ADSC) is an intriguing alternative. Using a model of a toxic liver damage in Sprague Dawley rats, generated by repetitive intraperitoneal application of retrorsine and allyl alcohol, the ability of human ADSC to support the restoration of liver function was investigated. A two-thirds hepatectomy was performed, and human ADSC were injected into one remaining liver lobe in group 1 (n = 20). Injection of cell culture medium performed in group 2 (n = 20) served as control. Cyclosporine was applied to achieve immunotolerance. Blood samples were drawn weekly after surgery to determine liver-correlated blood values. Six and twelve weeks after surgery, animals were sacrificed and histological sections were analyzed. ADSC significantly raised postoperative albumin (P < 0.017), total protein (P < 0.031), glutamic oxaloacetic transaminase (P < 0.001), and lactate dehydrogenase (P < 0.04) levels compared to injection of cell culture medium alone. Transplanted cells could be found up to twelve weeks after surgery in histological sections. This study points towards ADSC being a promising alternative to hepatocyte or liver organ transplantation in patients with severe liver failure.